Early Surgery Confers 1-Year Mortality Benefit in Hip-Fracture Patients. Issue 3 (March 2018) - Maheshwari, Kamal; Planchard, Jeffrey; You, Jing; Sakr, Wael Ali; George, Jaiben; Higuera-Rueda, Carlos A.; Saager, Leif; Turan, Alparslan; Kurz, Andrea
Abstract : Background: To evaluate the relationship between surgical timing and 1-year mortality in patients requiring hip fracture repair. Methods: We analyzed all 720 patients (>65 years) who had hip fracture surgery between March 2005 and February 2015, identifying patients by ICD-9 diagnosis and procedure codes using electronic data query. Mortality data were obtained from the institutional database, state and Social Security Death Indices. The relationship between surgical timing (defined as the interval from admission to the start of surgery) and 1-year mortality was assessed using a multivariable logistic regression, adjusting for baseline clinical status and surgical factors. Results: Among the 720 patients, 159 patients (22%) died within 1 year. The median time from admission to surgery was 30 hours. A linear relationship between the surgical timing and 1-year mortality was demonstrated. Delaying surgery was significantly associated with increased 1-year mortality, odds ratio 1.05 (95% CI: 1.02–1.08) per 10-hour delay ( P = 0.001). Conclusions: A linear relationship was observed between surgical timing and 1-year mortality. Each 10-hour delay from admission to surgery was associated with an estimated 5% higher odds of 1-year mortality. Therefore, we suggest that hip fractures should be treated urgently similar to other time-sensitive pathology such as stroke and myocardial ischemia. Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.